Military career of Junius Caesar - Hoop, C.H. (My University, 1897)
Introduction: Julius Caesar was born at Rome on the 4th of the Ides of Quintilis or July 12, 654. His father was C. Julius Caesar a Praetor who died suddenly at Pisa in 670 His mother was Aurelia descended from an illustrious Plebeian family. His mother was a high minded and moral woman and his success in his later life was largely due to the training he received from her. He was a nephew to Marius the great popular leader. From this relationship he was strongly attached to the popular cause. His leaning towards this cause was further increased by his marriage with Cornelia the daughter of Cinna. When Sulla became dictator he ordered several of the doubtful patricians to divorce their wives. Among them he ordered Caesar to divorce Cornelia. This Caesar refused to do and in consequence had to flee into hiding for his life. He was eventually pardoned, but Sulla is reported to have said when he granted the pardon, “Well! Be it so, you will it; but know that he, whose pardon you demand, will one day ruin the party of the great for which we have fought together, for, trust me, there are several Mariuses in this young man.” Caesar is one of the few who opposed the dictators wrath and lived.
Citation: Hoop, C.H. Military career of Junius Caesar. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Julius Caesar; History; Military; Theses; Manuscripts (documents)